Implikasi Perancangan Kontrak Terhadap Pencegahan Wanprestasi: Analisis Kritis Putusan Perkara Nomor 171/PDT.G/2020/PN.JKT.SEL - Ariani, Lillah; Jamaica, Jingga Ajeng Muda; Awalia, Sahihah Anik; Mujib, Rayi Kharisma (Faculty of Law, Diponegoro University, 2025)
Weaknesses in contract drafting often cause legal uncertainty and lead to breach of contract disputes. This study focuses on South Jakarta District Court Decision No. 171/Pdt.G/2020/PN.Jkt.Sel. to analyze how inadequate drafting contributes to contractual violations and how it can be prevented. The research aims to identify the legal principles neglected in the case and to propose preventive measures for improving contract drafting quality. Using a normative juridical method with statutory and case approaches, the study examines the imbalance of legal positions, ambiguity of clauses, and disregard of fundamental principles such as good faith and contractual justice. The findings show that poor drafting and unequal bargaining positions weaken the binding force of agreements, resulting in breach of contract. The study concludes that applying prudential drafting principles and proportional supervision is essential to ensure fairness, legal certainty, and the prevention of similar contractual disputes.